Back Cover: Metabolic Instability of Cyanothiazolidine‐Based Prolyl Oligopeptidase Inhibitors: a Structural Assignment Challenge and Potential Medicinal Chemistry Implications (ChemMedChem 7/2015). Issue 7 (July 2015) - Schiavini, Paolo; Pottel, Joshua; Moitessier, Nicolas; Auclair, Karine
<x xml:space="preserve">Abstract</x> The back cover picture shows the computed transition state for P450‐mediated sulfur oxidation of a prolyl oligopeptidase (POP) inhibitor. P450 metabolism generates a dynamic mixture of diastereomers. The structure identification puzzle was solved by translating experimental results into a computational protocol aimed at considering all possible combinations of diastereomers to narrow it down to one. For further details, see the Full Paper by Paolo Schiavini, Joshua Pottel, Nicolas Moitessier, Karine Auclair on p. 1174 ff.